Shoulder pain in badminton players and wrestlers - Sundström, A.; Tärnklev, C.; Fahlström, M. (International Journal of Racket Sports Science, 2024)
The purpose of the study was to study painful conditions in the shoulders among badminton players, to describe them and compare with wrestlers. Testing was conducted on 63 badminton players and 56 wrestlers with Constant Score and a shoulder injury questionnaire. Previous or on-going shoulder pain was reported by 29 (46%) of the badminton players - 24 (48%) male and 5 (38%) female and by 30 (54%) of the wrestlers - 20 (63%) male and 10 (42%) female. Three badminton players (5%) had on-going shoulder pain, while eighteen of the wrestlers (32%) had on-going shoulder pain (p=<0.001, f=-0.36). More male than female wrestlers had on-going shoulder pain [14 (44%) vs. 4 (17%), (p=0.032, f=0.29)]. In badminton players the shoulder pain was located to subacromial structures in the dominant shoulder, while the distribution of shoulder pain in wrestlers was widespread and included both dominant and non-dominant side on various locations. Male wrestlers with on-going shoulder pain had a higher BMI compared to male wrestlers without on-going shoulder pain [25.2±2.6, 25 kg/m² vs. 23±2.3, 23 kg/m² (p=0.011, r=0.44)], while female wrestlers with ongoing pain had a lower BMI compared to pain-free female wrestlers [19.4±2, 18.9 kg/m² vs. 21.7±2.1, 22.2 kg/m² (p=0.045, r=0.41)]. The badminton players in this study had a lower prevalence of on-going shoulder pain compared to in previous studies on badminton players. Wrestlers with on-going shoulder pain had lower scores for shoulder mobility in several directions compared to pain-free wrestlers. On-going shoulder pain is likely to affect sports performance and might lead to development of other injuries.